Diversity and biomass of terrestrial small mammals at a Malaysian primary rainforest reserve (Segari Melintang Forest Reserve, Peninsular Malaysia) - Nadine Ruppert; Asyraf Mansor; Shahrual MS Anuar (Journal of Tropical Life Science, 2015)
Despite their importance for the rain forest ecosystem, still not much known about the community composition of small frugivorous mammals in West-Malaysian forests. Therefore, we conducted a mark and recapture study in four 100 m x 100 m sized plots in a lowland Dipterocarp forest of Peninsular Malaysia for 4000 trap nights. Plots hosted either Dipterocarp forest or alluvial fresh water swamp vegetation. We assumed that small mammal assemblages varied between these two vegetation types. In total 249 different individuals of 14 species (9 genera) were caught, comprising rodents and treeshrews. The most abundant species was the common tree shrew (Tupaia glis, 25.8 individuals ha-1), followed the plantain squirrel (Callosciurus notatus, 10.25 individuals ha-1) and the grey tree rat (Lenothrix canus, 10.0 individuals ha-1). These three species accounted for 77.8% of the total small mammals biomass per hectare. Sex-ratio of treeshrews and squirrel species was found at 1:1, whereas Muridae showed male-biased sex-ratios. Shannon-diversity indices (H) of all trapping plots ranged at mediocre level. Plot comparison (Bray-Curtis indices) showed that plots with similar vegetation types were not more similar in their small mammal community structure. Other factors, such as distance to the forest edge and joining oil palm plantations seemed to influence species abundances. Small mammals belong to the less studied species in local rain forests, thus studying their ecology is vital in order to act towards general conservational issues.